Wild avian species diversity and abundance at Al Ain Zoo in the United Arab Emirates (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chanyandura A, Alhajeri MM, Alqahtani HA, Alotaiba AM, Khan MAR. 2025. Wild avian species diversity and abundance at Al Ain Zoo in the United Arab Emirates. Biodiversitas 26: 3397-3407. Al Ain Zoo in the United Arab Emirates, serves as an important habitat for diverse bird species, providing a safe refuge and breeding ground for resident and migratory birds. Birds play an important role as bioindicators in different ecosystems. The primary objective of this study was to explore species diversity, frequency of occurrence, richness, and evenness in four habitat categories and land use zones, namely Safari, United Arab Emirates World Desert, Core Zoo, and Back of House in Al Ain Zoo. The data was collected using the line transect method in predetermined zones over seven years. A total of 106,288 records of single bird detection and 136 bird species were documented from 2017 to 2023, including breeding birds, non-breeding birds, and migratory birds. The data exhibited a fluctuating trend, starting with a sharp increase from 4,422 to 11,348 birds, a decline to 6,856, and then a recovery to 14,970. The decline can be attributed to the COVID-19 pandemic and other environmental changes. The most recent years (2022 and 2023) indicate a robust upward trajectory. Welch's ANOVA revealed a significant difference in species richness among the areas (FWelch (3, 13.19): 14.83, p
Keywords: Bioindicators, ecological index, habitat, Principal Component Analysis